Impact of inoculum source and primary carbon source on biotransformation of pharmaceuticals and personal care products - Kim, Sunah, author; De Long, Susan, advisor; Sharvelle, Sybil, committee member; Omur-Ozbek, Pinar, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.
Keywords: inoculum source; pharmaceuticals and personal care products; biotransformation; primary carbon source; microbial community